FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DAGING SAPI DI PASAR RAYA I SALATIGA - Ega Jalu Nugroho; Liska Simamora (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Pasar Raya 1 is one of the traditional markets located in the city of Salatiga. Pasar raya 1 is located on Jl. Jend. Sudirman, Kutowinangun Kidul Kec. Tingkir, Salatiga City, Central Java. Pasar Raya. This study aims to identify consumer characteristics, analyze the effect of price, service quality, lifestyle, product quality, place, promotion. This research was conducted in August - December 2020 in the City of Salatiga. This type of research uses quantitative descriptive, the sampling method used in this research is purposive sampling by determining criteria, namely anyone who has made a purchase and is willing to be interviewed. Samples were collected as many as 70 respondents, namely the criteria for beef consumers in Pasar Raya 1. The analytical method used is multiple regression analysis techniques. The results showed that: 1. The  Characteristics of the most respondents, 64 (93%) were female, 32 (45.7%) aged 40-49 years, based on the education level of 26 people (37.1%) SMA, the factors that have a significant effect are price (X1), product quality (X4), place (X5), while for service quality (X2), lifestyle (X3), promotion (X4), do not have a significant effect on purchasing decisions.